2016
DOI: 10.3892/mmr.2016.5341
|View full text |Cite
|
Sign up to set email alerts
|

SDF-1/CXCR4 axis induces apoptosis of human degenerative nucleus pulposus cells via the NF-κB pathway

Abstract: Intervertebral disc degeneration (IVDD) is a major cause of lower back pain, and increased cell apoptosis is a key characteristic of IVDD. The present study aimed to investigate the effects and mechanism of the stromal cell-derived factor-1 (SDF-1)/C-X-C motif chemokine receptor 4 (CXCR4) axis on apoptosis in human degenerative nucleus pulposus cells (NPCs). The expression levels of SDF-1 and CXCR4 in human intervertebral discs (IVD) were determined using immunohistochemistry and western blot analysis. Apoptos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 25 publications
1
37
0
Order By: Relevance
“…Inhibiting the activation of NF-κB can significantly retard the degree of disc degeneration [13, 28]. It was also reported that the SDF-1/CXCR4 axis induces apoptosis of human degenerative NPCs via the NF-κB pathway [29]. Our results also indicated that the levels of apoptosis and P65 in degenerated intervertebral disc tissue were significantly higher than in normal intervertebral disc tissue, suggesting that the NF-κB signalling pathway was involved in NPC apoptosis.…”
Section: Discussionsupporting
confidence: 73%
“…Inhibiting the activation of NF-κB can significantly retard the degree of disc degeneration [13, 28]. It was also reported that the SDF-1/CXCR4 axis induces apoptosis of human degenerative NPCs via the NF-κB pathway [29]. Our results also indicated that the levels of apoptosis and P65 in degenerated intervertebral disc tissue were significantly higher than in normal intervertebral disc tissue, suggesting that the NF-κB signalling pathway was involved in NPC apoptosis.…”
Section: Discussionsupporting
confidence: 73%
“…The theme of the regulation of axonal plasticity by Calpain mediated mechanisms was also determined in studies involving the effect of SDF1 on axon development. SDF1 binds to the G-protein-coupled receptor C-X-C motif chemokine receptor 4 (CXCR4) (Liu et al, 2016), and regulates the development of the nervous system through effects on cell migration and axon guidance (Mithal, et al, 2012). A recent report provides evidence that SDF1 reduces branching in cortical interneuron through dual regulation of actin and microtubules.…”
Section: Signaling Mechanisms That Regulate Cytoskeletal Dynamics Durmentioning
confidence: 99%
“…In contrast, genetic heredity is the predominant risk factor for degenerative disc disease and is estimated to cause over 70% of cases . Although the pathogenesis of IDD is not completely understood, it is well established that progressive loss of ECM, cell proliferation, inflammatory response, angiogenesis, apoptosis, autophagy, and oxidative stress play critical roles in the occurrence and development of disc degeneration …”
Section: Role Of Lncrnas In Iddmentioning
confidence: 99%
“…40,41 Although the pathogenesis of IDD is not completely understood, it is well established that progressive loss of ECM, cell proliferation, inflammatory response, angiogenesis, apoptosis, autophagy, and oxidative stress play critical roles in the occurrence and development of disc degeneration. [42][43][44][45][46][47] Like the well-known short non-coding RNAs such as miRNAs, 1 49 Overexpression of FAF1 is known to potentiate Fas-mediated apoptosis and suppress the degradation of ubiquitinated proteins, leading to a significant increase of cell death. 50,51 These authors also found that in addition to upregulation of the nearby enhancer-like lncRNA, RP11-296A18.3, FAF1 is significantly increased in degenerative discs compared with the normal discs.…”
Section: Ivdmentioning
confidence: 99%